DINAMIKA SISTEM PENDIDIKAN ISLAM (SURAU) MINANGKABAU PRA DAN PASCA PEMBAHARUAN - Melia Afdayeni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
The existence of Islamic education institutions in Minangkabau has faced a very significant development. It was estimated as old as the Islamic age in this region (Minangkabau). Starting from the surau system of traditional education, Minangkabau succeed in producing the greatest scholars and Islamic intellectuals who have contributed in the development of Islam in the archipelago in the past. For more than three centuries ago, surau sytem have played an important role for the development of the scientific tradition in this country. Islamic intellectual tradition seems to have suitable place for the growth and development of all forms of Islamic tradition. Also, it produces the genius idea about Islam and eventually became an identity and entities of Islamic in Minangkabau. Thus, surau has functioned as a place of transformation of highly qualified Islamic scholarship.,/em> Eksistensi lembaga pendidikan islam di Minangkabau telah mengalami perkembangan yang sangat signifikan. Usianya diperkirakan setua usia Islam di wilayah ini (Minangkabau). Berawal dari sistem pendidikan tradisional surau, daerah Minangkabau berhasil melahirkan ulama-ulama besar dan intelektual Islam yang memiliki andil dalam perkembangan Islam di Nusantara pada masa lalu. Selama lebih dari tiga abad yang lalu, lembaga pendidikan surau telah memainkan peran penting bagi perkembangan tradisi keilmuan di negeri ini. Tradisi intelektual Islam seolah-seolah mendapat tempat yang sangat cocok untuk tumbuh dan berkembangnya segala bentuk tradisi keilmuan Islam dan banyak melahirkan ide jenius tentang keislaman yang pada akhirnya menjadi sebuah identitas dan entitas Islam di Minangkabau. Dengan demikian surau telah memainkan fungsinya sebagai tempat transformasi keilmuan Islam yang sangat mumpuni.